Accounting, auditing & accountability journal. (MCB University Press, 1988)
Accounting, Auditing & Accountability Journal publishes leading-edge research concerning the interaction between accounting/auditing and their socio-economic, institutional and political environments. Through innovation in research design and issue analysis, we encourage critical investigation of policy and practice alternatives and of the impact of accounting on organisations, communities and society. Our mission is to expand both an understanding of and creative solutions to important accounting, auditing and accountability topics.